Retraction notice. (August 2015) - Unknown
At the request of the Editor(s) and the Publisher and author(s), the following article "Differential Game Guidance Law for a Kinetic Kill Vehicle and Its Simulation" by Xing-Yuan Xu, Xiao-Na Song and Yuan-Li Cai. Simulation, first published June 10, 2015, DOI 10.1177/0037549715588839 . has been retracted. The Editor has judged that the paper plagiarized the following article, and the authors have agreed to their paper being retracted: "Linear Quadratic Guidance Laws for Imposing a Terminal Intercept Angle" by Vitaly Shaferman and Tal Shima, Journal of Guidance, Control, and Dynamics, Vol. 31, No. 5, DOI 10.2514/1.32836.